2021
DOI: 10.31486/toj.20.0164
|View full text |Cite
|
Sign up to set email alerts
|

Rare Case of Primary Pulmonary Pleomorphic Liposarcoma Treated With Multimodal Therapy

Abstract: Background: Pleomorphic liposarcoma (PLS) is a very rare type of primary pulmonary sarcoma. Clinical data about these tumors are limited, and optimal treatment has not yet been defined. Case Report: A 32-year-old male presented with pain and heaviness over the right chest. Contrast-enhanced computed tomography (CECT) of the chest showed a heterogeneous hypodense pleural-based mass and a mediastinal mass. The patient was treated with chemoradiotherapy, followed by excision and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…However, researchers suggest that pre-operative radiotherapy should be taken into consideration in these malignant lesions, in order to reduce the tumor volume and obtain surgical resection margins [ 69 ]. Among pleomorphic liposarcomas with peculiar locations, malignant adipocytic tumors of the viscera require special attention [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. We identified two primary pleomorphic liposarcomas of the lung, reported by Li B. et al and Dey T. et al, both of them identified in male patients with no history of smoking or alcohol abuse [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, researchers suggest that pre-operative radiotherapy should be taken into consideration in these malignant lesions, in order to reduce the tumor volume and obtain surgical resection margins [ 69 ]. Among pleomorphic liposarcomas with peculiar locations, malignant adipocytic tumors of the viscera require special attention [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. We identified two primary pleomorphic liposarcomas of the lung, reported by Li B. et al and Dey T. et al, both of them identified in male patients with no history of smoking or alcohol abuse [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among pleomorphic liposarcomas with peculiar locations, malignant adipocytic tumors of the viscera require special attention [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. We identified two primary pleomorphic liposarcomas of the lung, reported by Li B. et al and Dey T. et al, both of them identified in male patients with no history of smoking or alcohol abuse [ 71 , 72 ]. The patients presented with shortness of breath and chest pain, and the tumors were described as large, hypodense masses identified using a CT scan [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations